Economic evaluation of first-line sugemalimab plus chemotherapy for metastatic non-small cell lung cancer in China - Wang, Hao; Liao, Li; Xu, Yuan; Long, Yunchun; Wang, Ye; Zhou, Yujie (Frontiers in Oncology, 2022)
ABSTRACT OBJECTIVE: To evaluate the economics of sugemalimab plus chemotherapy in the first-line treatment of metastatic non-small cell lung cancer, and to provide a reference for the formulation of relevant medical insurance policies and rational drug use. METHODS: From the perspective of the Chinese health system, a three-state partitioned survival model was constructed based on data from a phase III randomized clinical trial (GEMSTONE 302) to evaluate the cost-utility of sugemalimab plus chemotherapy compared with chemotherapy in first-line treatment of metastatic non-small cell lung cancer. Model results were expressed as total cost, life years, quality-adjusted life years, and incremental cost-effectiveness ratio. The robustness of the underlying analysis results was verified using one-way sensitivity analysis and probabilistic sensitivity analysis. RESULTS: The results of the base-case analysis showed that sugemalimab plus chemotherapy yielded 1.63 QALYs at a total cost of 130,667.70 USD, chemotherapy yielded 1.04 QALYs at a total cost of 64,001.02 USD, and the ICER was 113,155.52 USD/QALY, which was well above the current willingness-to-pay threshold in China (3 times 2021 per capita GDP) (36,203.88 USD). CONCLUSION: This study suggests that sugemalimab in combination with a chemotherapy regimen is more effective but not economical for patients with metastatic non-small cell lung cancer receiving first-line therapy in China and that a reasonable reduction in drug prices could improve the probability of it being economical.